THE IMPORTANCE OF PROMOTING WELL-BEING AND MENTAL HEALTH IN THE WORKPLACE - Foliassa, Rafael Vieira; da Costa, Elvio Carlos (Revista Interface Tecnológica, 2024)
The present study aimed to investigate the promotion of well-being and mental health in the workplace, which has become an essential issue in human resources management practices. The study seeks to explore the main causes of mental health problems in organizations, understand their consequences on employee productivity, and identify the challenges companies face in implementing improvement actions. A bibliographic review was conducted, and two questionnaires were applied via Google Forms to 5 companies in the retail sector in the city of Araraquara, involving 5business owners and 25 employees. The data reveal that factors such as work overload, lack of recognition, and toxic environments significantly contribute to occupational stress. The study concludes that promoting well-being not only benefits employees but also strengthens organizational efficiency.